Positive Youth Development and Wellbeing: Gender Differences - Tomé, Gina; Gaspar de Matos, Margarida; Reis, Marta; Gomez-Baya, Diego; Coelhoso, Filipa; Wiium, Nora (Frontiers in Psychology, 2021)
The five C's of Positive Youth Development (competence, confidence, character, caring and connection) have been associated with adaptive development among young people. Gender differences in young people’s wellbeing and mental health have been studied and analysed, but their association with the five C´S is still at the beginning of their investigation. In the present study, we analysed the influence of the Five C`s on the well-being, more specifically, anxiety, social alienation, general well-being, physical symptoms and psychological symptoms, of Portuguese adolescents, by gender. Participants were 5th to 12th grade students attending public schools in Lisbon, Portugal. The questionnaire was administered to 384 adolescents. The results indicated important gender differences in young people’s well-being. The results reveal some differences between genders that should be considered in interventions that aim to promote the well-being of adolescents. On the other hand, confidence was positively associated with mental health and well-being for both boys and girls, skill that should be promoted among young people, because it was the competence that reveals the greatest association with well-being, among the variables analyzed.